Predictive factors for voiding dysfunction after transobturator slings - Lucas Schreiner; Thais Villela Peterson; Deborah Karp; Guillermo Willy Davila (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2013)
PURPOSE: To identify the predictive factors for voiding dysfunction after transobturator slings. METHODS: We retrospectively reviewed the records of all patients who underwent a transobturator sling between March 2003 and December 2008. A total of 514 women had available data with at least a six-week follow-up. Patients' demographics, preoperative symptoms, urodynamic testing including multichannel voiding studies and surgical variables were tabulated. Voiding dysfunction was defined by a catheterized or ultrasonographic postvoid residual greater than 100 cc (≥six weeks after the procedure) associated with any complaints of abnormal voiding. Univariate logistic regression analysis was performed with respect to postoperative voiding dysfunction. RESULTS: The patient population had a mean age of 58.5±12.9 years. Thirty-three out of 514 patients (6.4%) had postoperative voiding dysfunction according to our definition, and 4 (0.78%) required sling transection. No differences were observed between normal and dysfunctional voiders in age, associated prolapse surgery, preoperative postvoid residual, preoperative urinary flow rate, prior pelvic surgery, and menopausal status. Valsalva efforts during the preoperative pressure flow study was the only predictive factor for postoperative voiding dysfunction, 72.4% dysfunctional versus 27.6% normal (p<0.001). CONCLUSION: Preoperative Valsalva maneuver during the micturition could identify those at risk for voiding dysfunction after transobturator sling, and it should be noted during preoperative counseling.